Problem dan Tantangan Pembelajaran Kitab Kuning Di Indonesia (Tsamratul Fikri | Jurnal Studi Islam, 2022)
This study aims to elaborate on the problems and challenges of learning the yellow book or classical Islamic books. The study method used is literature review, in which relevant literature is collected, read, and analyzed to obtain conclusions that are academically justifiable. The results of the study show that among the problems and challenges faced by Muslims is the lack of human resources who have the ability to read the yellow book. This phenomenon then leads to the problems and challenges of learning the yellow book, namely the low interest of students in learning to read, understand, and explain the contents of the yellow book. This is also due to the fact that the ability to read the yellow book alone is seen as not promising a profession, a job, and a decent life. So that parents are more likely to send their children not to Islamic boarding schools that focus on studying the yellow book, but to general educational institutions, both schools and madrasas.